POSITION AND MANAGEMENT STRATEGY FOR PUBLIC GREEN OPEN SPACES IN THE CITY OF DENPASAR, BALI PROVINCE - Indrawati, Mei; Sudiana, AA.K.; Sumantra, K. (International Journal of Research -GRANTHAALAYAH, 2021)
Green Open Space "RTH" plays a very important role in realizing a sustainable city and has a balance of functions both ecologically and psychologically for urban communities. Green Open Space can be divided into two, namely public green open space and private green open space, but only public green open space can still be controlled directly by the government. The purpose of this study is to identify the availability of public green open space in the city of Denpasar and to formulate strategies and policies for managing public green open space in the city of Denpasar. Data collection techniques were carried out using interviews and questionnaires, qualitative and quantitative descriptive data analysis with SWOT analysis for the use of public green open space, and the Analytical Hierarchy Process (AHP) to determine management strategies and policies. The availability of public green open space in 2011 was recorded at 2,341.48 or 18.32 percent. The availability of public green open space in 2019 was recorded at 1,572,990 ha or 12.49 percent. The difference in 2011 and 2019 was 768,490 Ha or 5.83 percent. The minimum area for public green open space following the 20 percent rule is 1.68 percent (in 2011) and 7.51 percent (in 2019). The implementation of Denpasar Public Green Open Space (RTH) management has not met the standards of the Minister of Home Affairs Regulation Number 1 of 2007 and Minister of Public Works Number 5 of 2008. The strategy for managing Green Open Space is to develop detailed spatial plans, install information boards, enforce laws, and implement incentives disincentives to relevant stakeholders